Causal association between common rheumatic diseases and glaucoma: a Mendelian randomization study - Meng, Yang; Tan, Zongbiao; Su, Yu; Li, Lu; Chen, Changzheng (Frontiers in Immunology, 2023)
Background Autoimmunity and inflammation are the main characteristics of rheumatic diseases and have both been found to be related to glaucoma. However, it remains unclear whether rheumatic diseases increase the risk of glaucoma. Here, we performed a Mendelian randomization (MR) analysis to investigate the causal effects of six common rheumatic diseases on glaucoma. Methods Six rheumatic diseases were included: ankylosing spondylitis (AS), rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), Sicca syndrome/Sjögren’s sydrome (SS), dermatomyositis (DM), and gout. Glaucoma included primary open-angle glaucoma (POAG) and primary angle-closure glaucoma (PACG). Genetic variants associated with these rheumatic diseases and glaucoma were extracted from the genome-wide association studies and FinnGen8 database, respectively. First, a two-sample MR was used to investigate the potential causal association. Then, a multivariable MR was conducted to further verify the results. Inverse-variance weighted MR analysis was used as the main method, together with several sensitivity analyses. Results Two-sample MR suggests that AS is related to a higher risk of both POAG [odds ratio (OR): 1.28, 95% confidence interval (CI) 1.13–1.44; p = 1.1 × 10−4] and PACG (OR: 1.55, 95% CI: 1.09–2.09, p = 1.4 × 10−2). Multivariable MR shows a similar trend of the effect of AS on POAG (OR: 1.52, 95% CI: 1.22–1.90, p = 1.9 × 10−4) and PACG (OR: 2.05, 95% CI: 1.06–3.95, p = 3.2 × 10−2). No significant association was observed between the other five rheumatic diseases and glaucoma. Conclusions AS is related to an increased risk of POAG and PACG. We stress the importance of glaucoma screening for AS patients.